UNIT 21.2 Practical Integration‐Free Episomal Methods for Generating Human Induced Pluripotent Stem Cells. (6th October 2015) - Kime, Cody; Rand, Tim A.; Ivey, Kathryn N.; Srivastava, Deepak; Yamanaka, Shinya; Tomoda, Kiichiro
Abstract : The advent of induced pluripotent stem (iPS) cell technology has revolutionized biomedicine and basic research by yielding cells with embryonic stem (ES) cell‐like properties. The use of iPS‐derived cells for cell‐based therapies and modeling of human disease holds great potential. While the initial description of iPS cells involved overexpression of four transcription factors via viral vectors that integrated within genomic DNA, advances in recent years by our group and others have led to safer and higher quality iPS cells with greater efficiency. Here, we describe commonly practiced methods for non‐integrating induced pluripotent stem cell generation using nucleofection of episomal reprogramming plasmids. These methods are adapted from recent studies that demonstrate increased hiPS cell reprogramming efficacy with the application of three powerful episomal hiPS cell reprogramming factor vectors and the inclusion of an accessory vector expressing EBNA1. © 2015 by John Wiley & Sons, Inc.